"Being on the walk put it somewhere in my body": The meaning of place in health for Indigenous women. Issue 1 (2nd January 2021) - Fernandez, Angela R.; Evans-Campbell, Tessa; Johnson-Jennings, Michelle; Beltran, Ramona E.; Schultz, Katie; Stroud, Sandra; Walters, Karina L.
ABSTRACT: Relationship to place is integral to Indigenous health. A qualitative, secondary phenomenological analysis of in-depth interviews with four non-Choctaw Indigenous women participating in an outdoor, experiential tribally specific Choctaw health leadership study uncovered culturally grounded narratives using thematic analysis as an analytic approach. Results revealed that physically being in historical trauma sites of other Indigenous groups involved a multi-faceted process that facilitated embodied stress by connecting participants with their own historical and contemporary traumas. Participants also experienced embodied resilience through connectedness to place and collective resistance. Implications point to the role of place in developing collective resistance and resilience through culturally and methodologically innovative approaches.